Determining factors in Mexican skilled migration to the United States. A systematic review - González-Ahumada, Solangel (Política, Globalidad y Ciudadanía, 2024)
The main objective of this article is to analyze the empirical scope within the scientific literature on the determining factors of Mexican skilled migration to the United States. Using the methodology of systematic reviews, searches were carried out for scientific articles published between 2013 and 2023, in Spanish and English. Through 5 electronic databases: Scientific Electronic Library Online (Scielo), Google Scholar, Network of Scientific Journals of Latin America and the Caribbean, Spain and Portugal (Redalyc), Directory of Open Access Journals (DOAJ) and Education Resources Information Center (ERIC). Within the search, Boolean operators AND and OR were used, including 90 studies published in indexed journals. In addition, specific criteria were used to select the research that described the profile of qualified Mexican migrant with undergraduate or graduate studies. For the final analysis, 9 studies were included, and the findings obtained through the available evidence indicate that the determining factors in Mexican qualified migration to the United States are mainly labor, economic, salary, due to structural weaknesses in science and technology and academics. Family indicators, insecurity and professional development were found less frequently.